2020
DOI: 10.1111/jonm.12938
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of stress management interventional programme on occupational stress for nurses: A systematic review

Abstract: Aim The purpose of this systematic review is to evaluate the effectiveness of stress management interventional programme in reducing occupational stress among nurses. Background Nursing professionals are placed continuously at the forefront in the area of health care which makes them highly exposed to professional stress. Evaluation Randomized controlled trial studies (RCTs) were systematically searched in eight different databases for works published in English from 2011 to 2019; inclusion criteria were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
(230 reference statements)
0
25
0
Order By: Relevance
“…In addition to applying stress management interventions to reduce stress [18], as recommended by Happell et al [19], an initial step toward reducing occupational stress is to understand the stressors present in nurses' work environments as well as the methods through which these stressors may be eliminated. Not only qualitative researches have been performed to look for nursing stressors [19,20], but several self-report scales have been developed to measure nursing stress indicators in hospital environment, such as Expanded Nursing Stress Scale (ENSS) [21], and Practice Environment Scale of the Nursing Work Index [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to applying stress management interventions to reduce stress [18], as recommended by Happell et al [19], an initial step toward reducing occupational stress is to understand the stressors present in nurses' work environments as well as the methods through which these stressors may be eliminated. Not only qualitative researches have been performed to look for nursing stressors [19,20], but several self-report scales have been developed to measure nursing stress indicators in hospital environment, such as Expanded Nursing Stress Scale (ENSS) [21], and Practice Environment Scale of the Nursing Work Index [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing is acknowledged to be stressful work (Abualrub & Al‐zaru, 2008; Cox et al., 1996), and work stress in nursing is already of global concern (Happell et al., 2013). It is estimated that 70% of nurses suffer from stress (Alkhawaldeh et al., 2020). Maharaj et al.…”
Section: Introductionmentioning
confidence: 99%
“…Work stress is associated with physical and mental health outcomes (Khamisa et al., 2015). Numerous studies have shown that work stress significantly influenced nurses' burnout, musculoskeletal disorders, poorer self‐perceived health, social support, self‐efficacy, absenteeism and job satisfaction (Alkhawaldeh et al., 2020; Cox et al., 1996; Hayes et al., 2015; Khamisa et al., 2015; Liu & Aungsuroch, 2019; Tab ak & Orit, 2007). Stress in the workplace has a negative effect on nursing well‐being outcomes (Farquharson et al., 2013; Tab ak & Orit, 2007; Teo et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations